Effect of 8 Weeks Exercise on Irisin in Obese Women - Vahid Sari-Sarraf; Saeid Nikoukheslat; Zahra Niknam (Journal of Women's Reproductive Health, 2017)
Background The prevalence of obesity and type 2 diabetes is escalating at an alarming rate in many developed as well as developing countries. Irisin is a novel muscle and adipose drived chemokine that is, proteolytically processed from the product of the FNDC5 (fibronectin type ш domain containing 5) gene. The purpose of this study is to examine the effect of three kind of training on irisin in sedentary obese women. METHODSː33 obese women (medium age: 37.99 ± 3.7 year, height: 1.55 ± 0.03 meter, BMI: 34.6 ± 5.07 kg/m2) participated in the study, on three groups, including endurance, resistance and concurrent. Results After 8 weeks exercise we did not find significant differences in fasting glucose, insulin, HOMA-IR and irisin between the groups (P>0.05), but glucose and insulin in resistance groups and irisin in all groups had significant changes (P<0.05). Conclusions In summery in this study in contrast to hypothesis there were no difference between groups of training. It can be hypothesise that the increase of irisin in obese people is one of the preventing ways against of obesity's side effects. Exercise could improve the signaling pathways and consume the fat accumulations, therefore at the end of exercise duration, irisin decreased.
Keywords: Exercise